Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Consider the DE: $y''$ + $2\lambda y'$ + $\lambda^2$$y$ = $0$ subject to boundary conditions: $y(1) + y'(1) = 0$ and $3y(2) + 2y'(2) = 0$. The problems asks to find eigenvalues and eigenfunctions of the given BVP.

My approach: Obviously, The characteristic eqn gives $r = - \lambda$. So general solution is $y(x) = c_1e^{-\lambda x} + c_2xe^{-\lambda x}$. and by applying boundary condition, I obtain the following system:

$c_1(1 - \lambda) + c_2(2 - \lambda) = 0$

$c_1(3 - 2\lambda) + 4c_2(1 - \lambda) = 0$

From here, Im having difficulties in obtaining eigenvalues. I would to ask If my approach is correct or If I am probably doing something incorrect. Is there a better way to solve this problem?

thanks

share|improve this question
    
You mean $y(x) = c_1 e^{-\lambda x} + c_2 xe^{-\lambda x}$. –  Stefan Smith Oct 13 '12 at 0:30
    
corrected...... –  Chasky Oct 13 '12 at 0:30
    
You need to correct your system. It should contain $e^{-\lambda}$ and $e^{-2\lambda}$. –  Stefan Smith Oct 13 '12 at 1:10
    
@bogus can you explain how they would be in the equation. I think they cancel out –  Chasky Oct 13 '12 at 1:13
    
Yeah, you're right. Sorry. I'm used to problems where the exponential doesn't disappear. –  Stefan Smith Oct 13 '12 at 1:17
show 1 more comment

1 Answer 1

up vote 1 down vote accepted

Now, you have the system

$$ c_1(1 - \lambda) + c_2(2 - \lambda) = 0 \,,$$

$$ c_1(3 - 2\lambda) + 4c_2(1 - \lambda) = 0 \,. $$

Since you are solving for $c_1$ and $c_2$, then in order to get a non trivial solution for the system, you need to assume the determinant equals to zero. Doing that, you get the following values for lambda

$$ \lambda = \frac{3}{4}-\frac{i}{4}\sqrt{7}, \frac{3}{4}+\frac{i}{4}\sqrt{7}\,. $$

share|improve this answer
    
Are you sure these are solutions for lambda? –  Chasky Oct 13 '12 at 0:55
    
@LJym89:Try calculate the determinant. –  Mhenni Benghorbal Oct 13 '12 at 0:58
    
$4(1 - \lambda)^2 - (2 - \lambda)(3 - 2 \lambda) = 0$ –  Chasky Oct 13 '12 at 0:59
    
@LJym89: Your are right. There is a mistake. –  Mhenni Benghorbal Oct 13 '12 at 0:59
    
$\lambda = 1/4 +- \sqrt{17}/4$ I think these are the only two solutions. –  Chasky Oct 13 '12 at 1:01
show 5 more comments

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.